1985
DOI: 10.1152/ajprenal.1985.249.6.f819
|View full text |Cite
|
Sign up to set email alerts
|

Role of renal nerves in maintaining sodium balance in unrestrained conscious rats

Abstract: This study was designed to investigate the effects of bilateral renal denervation on sodium and water balance, the renin-angiotensin system, and systemic blood pressure in unrestrained conscious rats maintained on a normal- or low-sodium diet. Renal denervation was proven by chemical and functional tests. Both bilaterally denervated rats (n = 18) and sham-denervated rats (n = 15) maintained positive sodium balance while on a normal sodium intake. Both groups were in negative sodium balance for 1 day after diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
1

Year Published

1986
1986
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 0 publications
2
13
1
Order By: Relevance
“…However, as the deviation in sodium balance was transient, this is unlikely to explain the chronic decrease in MABP. In the absence of lasting changes in sodium balance (compared to the steady positive balance of appropriate control animals), the present 20% decrease in PRC, confirming previous results of renal denervation (8,18), does not provide a convincing explanation of the relative hypotension. Only further studies, including measurements of sympathetic tone and vasoactive hormones, may disclose these mechanisms.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…However, as the deviation in sodium balance was transient, this is unlikely to explain the chronic decrease in MABP. In the absence of lasting changes in sodium balance (compared to the steady positive balance of appropriate control animals), the present 20% decrease in PRC, confirming previous results of renal denervation (8,18), does not provide a convincing explanation of the relative hypotension. Only further studies, including measurements of sympathetic tone and vasoactive hormones, may disclose these mechanisms.…”
Section: Discussionsupporting
confidence: 64%
“…Other results have shown a modest decrease in systolic blood pressure (by tail cuff) after renal denervation (8). However, the time course of the development of hypotension after renal denervation has been unclear.…”
Section: Discussionmentioning
confidence: 93%
“…This may be due, in part, to the methods used to measure arterial pressure and how these measurements influence basal sympathetic activity. Such studies have included anesthetized surgically stressed animals (3), tail cuff measurements in conscious restrained rats (17), and direct recordings of arterial pressure in conscious tethered rats (21) or dogs (35). The strongest demonstration of how measurement conditions alter the influence of renal nerves on renal function comes from studies in conscious rabbits, in which renal nerve activity and renal blood flow were measured simultaneously in one kidney and blood flow was measured in the contralateral denervated kidney.…”
Section: Effect Of Bilateral Renal Denervation On Long-term Basal Levmentioning
confidence: 99%
“…A second possibility is that the reninangiotensin system is suppressed in RDNX rats, lowering arterial pressure. Several (7,17,20,35), but not all (19,21), investigators have reported that RDNX animals have low plasma renin activity compared with intact animals. In a recent study (11), we reported that Sham Fig.…”
Section: Potential Mechanisms Of Hypotension In Rdnx Ratsmentioning
confidence: 99%
See 1 more Smart Citation